Field reports, Eugene and Eloise Armstrong, fall 1990 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1990)
Field reports form (handmade) submitted by Eugene and Eloise Armstrong for fall 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed/flatbed